PERAN BRAND AWARENESS MEMEDIASI PENGARUH IKLAN TERHADAP NIAT BELI (STUDI PADA PRODUK PASTA GIGI MEREK SENSODYNE DI KOTA DENPASAR) - Dewi, Vidya Chandra; Sulistyawati, Eka (E-Jurnal Manajemen, 2018)
The low public awareness in dealing with sensitive dental problems by using sensitive dentifrice-specific toothpaste products such as the Sensodyne brand makes low purchasing intentions for these products. Purchase intention on a product can be improved by taking into consideration factors that can drive the purchase intention. The purpose of this study is to explain the role of brand awareness in mediating the effect of advertising on purchase intentions. The location of the study was held in Denpasar City involving 150 respondents with the method used is purposive sampling. This method was chosen because it is not known exactly the number of population. Data collection was done through questionnaires. Path analysis technique and sobel test were selected in analyzing data. The results of the study found that advertising has a positive and significant impact on brand awareness. Advertising has a positive and significant impact on purchase intention. Brand awareness has a positive and significant impact on purchase intention. Brand awareness mediates the effect of advertising on purchase intention. Sensodyne parties are expected to maintain and even improve the quality of advertising, so it can cause purchase intention to consumers through high brand awareness level.